2019
DOI: 10.1111/jdi.12996
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy of glutamic acid decarboxylase 65 autoantibody results between RSR radioimmunoassay and enzyme‐linked immunosorbent assay in patients with type 1 diabetes is related to autoantibody affinity

Abstract: Aim/Introduction Autoantibodies to the 65 kDa isoform of glutamic acid decarboxylase (GADA) are a valuable diagnostic and predictive marker for type 1 diabetes. Recently, it has been reported that a significant proportion of sera in the commercial RSR radioimmunoassay (RIA) that have tested positive for GADA have then turned negative in RSR enzyme‐linked immunosorbent assay (ELISA) tests in patients with type 1 diabetes. The present study aimed to investigate whether the GADA result discrepancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…The serum GADAb titers were measured using a commercial RIA and 125 I‐labeled recombinant human GAD65 as the tracer reagent (Cosmic); patients with GADAb titers of ≥1.5 U/mL (mean in Japanese controls + 3 SD) were judged as being positive, in accordance with previous reports. The GADAb titers in the same serum specimens were then measured by ELISA using the GADAb ELISA kit (Cosmic), and patients with GADAb titers of ≥5.0 U/mL (99th percentile of the 300 normal controls) were judged as being positive, in accordance with previous reports.…”
Section: Methodsmentioning
confidence: 59%
“…The serum GADAb titers were measured using a commercial RIA and 125 I‐labeled recombinant human GAD65 as the tracer reagent (Cosmic); patients with GADAb titers of ≥1.5 U/mL (mean in Japanese controls + 3 SD) were judged as being positive, in accordance with previous reports. The GADAb titers in the same serum specimens were then measured by ELISA using the GADAb ELISA kit (Cosmic), and patients with GADAb titers of ≥5.0 U/mL (99th percentile of the 300 normal controls) were judged as being positive, in accordance with previous reports.…”
Section: Methodsmentioning
confidence: 59%
“…In the present participants, there were no GADA‐ELISA‐negative participants with HLA‐DRB1*09:01 or HLA‐DQB1*03:03. It might be related to the divergence in HLA we reported and the divergence in the affinity of GADA Kawasaki et al . reported.…”
Section: Discussionmentioning
confidence: 78%
“…In the present participants, there were no GADA-ELISA-negative participants with HLA-DRB1*09:01 or HLA-DQB1*03:03. It might be related to the divergence in HLA we reported and the divergence in the affinity of GADA Kawasaki et al 13 reported. A larger study is required to verify that GAD-antibody-positive people with these HLA genotypes will necessarily become positive on a GADA-ELISA.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations